The Future of Democratic Capitalism - Arnold, Thurman W. (Benjamin Franklin Lectures of the University of Pennsylvania Ser., 2017)
The Future of Democratic Capitalism poses this question: what are the chances of survival for America's present economic and political way of life? Opposing totalitarian communism proclaimed by the USSR stands the democratic capitalism of the United States, which is being attacked from within as well as from without, and is undergoing such serious, rapid changes that its fundamental nature has been altered within a single generation. Between these two extremes stand the democratic and socialist nations of western Europe. The maintenance of the status quo is a challenge to all concerned, a challenge as difficult and dangerous as it is vital in character. And the best approach to the uncertain future of democratic capitalism would seem to be through a better understanding of the chief institutions of our present economic order. In this volume five distinguished authorities examine some of our most pressing problems.